Laryngitis caused by Talaromyces marneffei in a child - Chunyan Gao; Wujun Jiang; Chuangli Hao; Yuqing Wang (IDCases)
In this report evaluated a child was diagnosed with Talaromyces marneffei laryngitis with typical pictures.The classical laryngeal lesions caused by Talaromyces marneffei in our case are both educational and interesting.This report would help clinicians recognize laryngitis which caused by Talaromyces marneffei.